DINAMIKA PENGELOLAAN SUMUR MINYAK TRADISIONAL DI RANTO PEUREULAK ACEH TIMUR - Rangkuty, Rakhmadsyah Putra; Ketaren, Amiruddin; Hidayat, Hidayat; Hidayat, Bimby; MR, M. Husen (FISIP Universitas Malikussaleh, 2024)
This study was motivated by the existence of illegal oil drilling activities that have been going on for a long time and pose a high risk to the safety of workers, even local residents. Even though oil well fires often occur and victims suffer from burns and even death, this activity still continues. This research uses a qualitative approach, with a case study type of research based on observation, interview and documentation data. Meanwhile, technical analysis is carried out through Narrative Analysis. The research results show that the phenomenon of drilling old oil wells in Buket Pala Village has been carried out for decades. Mining workers have been able to utilize available resources so that they have more economic value. The old oil well has become the lifeblood of the village community. It is good for the mining community as well as for residents who receive an abundance of oil proceeds from